Pelatihan “PLANS” untuk Meningkatkan Efikasi Diri dalam Pengambilan Keputusan Karir - Difa Ardiyanti; Asmadi Alsa (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Self-efficacy has an important role in career decision-making. The collected data showed that there were some students (grade 11 and grade 12) had confused to decide their career choice. The data proved that career guidance is necessary for high school students. If students get assistance earlier, students will be more confident to make career decisions in their future. Therefore, the \